The research on a novel structure of two‐layer distributed controllers in software‐defined networking. Issue 3 (27th December 2017) - Dong, Ligang; Yang, Dandan; Guo, Kaiqiang; Fei, Shuocheng; Li, Ying; Wang, Weiming
Summary: Distributed controllers have been proposed for solving the scalability and reliability of the centralized controllers problems in software‐defined networking. This paper has presented a new two‐layer distributed controller structure Cacc with the features of overlap management and dynamic management. Cacc has advantages of load balancing and manageability. Furthermore, this paper has conducted the performance modeling of controller topologies and has proposed a new placement problem for Cacc: capacitated multi‐controller placement problem, in which one local controller is assigned to 2 or more root controllers with capacity limitation to achieve a high reliability. Both of the analysis and experiment results have verified the reliability advantages of capacitated multi‐controller placement problem. Abstract : This paper presented a new two‐layer distributed controller structure Cacc with the features of overlap management and dynamic management. Furthermore, this paper conducted performance modeling of controller topologies and proposed a new placement problem for Cacc: capacitated multi‐controller placement problem (CMCPP), in which one local controller is assigned to two or more root controllers with capacity limitation to achieve an high reliability. Both of the analysis and experiment results verified the reliability advantages of CMCPP.